DOUBLE CONCERTO FOR OUD AND CELLO MANIFESTASI MUSIKAL TERHADAP PERKEMBANGAN MUSIK BARAT DI PONTIANAK - Ahmad Muhajir; Aloysius Mering; Asfar Muniir (Universitas Tanjungpura, 2019)
AbstractThe musical composition of Double Concerto for Oud and Cello is a musical manifestation of the development of western music in Pontianak. Concerto is a form of western music in which there is a soloist as the principal role that is accompanied by orchestra. The cornerstones of the theories as a reference in term of music creation are concerto, music composition, elements of music composition, music composition techniques, and the writing of music notation. This composition, the music, consists of three movements. The method used in creating the music is transference. The creation stage uses several steps namely, observation, exploration, composition, and evaluation. As an absolute music, the discussion and analysis that the author focuses on each movement is on tone and harmony processing, rhythmic processing, timbre processing, tempo processing and tension, and music form. This piece is expected to provide an insight in the development of music science, especially in the form of concerto music and how to compose music through the traditional instruments of West Kalimantan and Western instruments.Keyword: Manifestation, double concerto, oud, cello